2012
DOI: 10.1007/s11262-012-0864-0
|View full text |Cite
|
Sign up to set email alerts
|

Full genome analysis of a novel type II feline coronavirus NTU156

Abstract: Infections by type II feline coronaviruses (FCoVs) have been shown to be significantly correlated with fatal feline infectious peritonitis (FIP). Despite nearly six decades having passed since its first emergence, different studies have shown that type II FCoV represents only a small portion of the total FCoV seropositivity in cats; hence, there is very limited knowledge of the evolution of type II FCoV. To elucidate the correlation between viral emergence and FIP, a local isolate (NTU156) that was derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). Detailed sequence analyses of numerous serotype II FCoVs revealed that the 5 0 -recombination event occurs in the polymerase gene while the 3 0 -recombination site is located in the E or M genes.…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 66%
See 3 more Smart Citations
“…There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). Detailed sequence analyses of numerous serotype II FCoVs revealed that the 5 0 -recombination event occurs in the polymerase gene while the 3 0 -recombination site is located in the E or M genes.…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 66%
“…Furthermore, serotype II FCoVs have predominantly been observed in Asia and they were reported to be responsible for up to 25% of the natural infections in those countries (Amer et al, 2012;An et al, 2011;Sharif et al, 2010). There is consistent evidence from independent studies that serotype II viruses emerge via double homologous recombination between serotype I FCoV and CCoV Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014). As a consequence of the recombination, approximately one-third (10 kb) of the serotype I FCoV genome including the S gene and the neighboring regions are replaced with the equivalent parts of the CCoV genome Haijema et al, 2007;Herrewegh et al, 1998;Lin et al, 2013;Lorusso et al, 2008;Terada et al, 2014).…”
Section: Fcov Serotypes and Cellular Receptor Usagementioning
confidence: 99%
See 2 more Smart Citations
“…The genome of FIPV contains a positive-sense, single-stranded RNA that is approximately 29,000 nucleotides in length, with 11 open reading frames (ORFs) encoding structural, non-structural, and accessory genes (Pedersen, 2009(Pedersen, , 2014aLin et al, 2013). Two-thirds of the FCoV genome at the 5' end comprise two overlapping ORFs, ORF1a and 1b, which encode two polyproteins.…”
Section: Introductionmentioning
confidence: 99%